If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 2(-3y) = 3 Remove parenthesis around (-3y) 3y + 2 * -3y = 3 Multiply 2 * -3 3y + -6y = 3 Combine like terms: 3y + -6y = -3y -3y = 3 Solving -3y = 3 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-3'. y = -1 Simplifying y = -1
| 9-4(2x-4)=89 | | 9-8=3 | | 5(3p+1)(p-3)(p+6)=0 | | q-8=3 | | 6(2r-4)-10=-106 | | n^2+7n+6=6 | | 126=-5x-9(-1-2x) | | m+29.6=50.4 | | -6(5n-6)+5=-189 | | 4Z+5=29 | | b-18=24 | | 4x+4(3x-14)=136 | | 5(5.81395348)-7(0.0116279)-800=0 | | -5x+34=59 | | 6x+21x-28=1-2x | | 47x+4y=47 | | 120y^6+48y^4= | | -207=-9n+9(-10n+10) | | 144=-8(3-3k) | | x-3/5=1+2/5 | | 59=b+14 | | 6(-10m-5)=-450 | | 17x+50=356 | | 2(3x+4)-6=10 | | -147=-7(1+5x) | | 7x-6=9x-8 | | 200=3x^2-50x+30 | | -88+9x=-2x+154 | | 5w^2+6=-13w | | 186=-6(10v+9) | | -88+9x=-2x+124 | | 144=-3(-6+6r) |